Cellular accumulation and cytotoxic effects of zinc oxide nanoparticles in microalga Haematococcus pluvialis - Djearamane, Sinouvassane; Lim, Yang Mooi; Wong, Ling Shing; Lee, Poh Foong (PeerJ, 2019)
Background Zinc oxide nanoparticles (ZnO NPs) are widely used in household and cosmetic products which imply an increased releasing of these particles into the environment, especially aquatic ecosystems, resulting in the need of assessing the potential toxic effects of ZnO NPS on the aquatic organisms, particularly on microalgae which form the base for food chain of aquatic biota. The present study has investigated the dose- and time-dependent cellular accumulation and the corresponding cytotoxic effects of increasing concentrations of ZnO NPs from 10–200 μg/mL on microalga Haematococcus pluvialis at an interval of 24 h for 96 h. Methods The scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX) was used to qualitatively detect the cellular accumulation of ZnO NPs in algal cells, while inductively coupled plasma optical emission spectrometry (ICP OES) was performed to quantify the cell associated-zinc in algal cells. The percentage of cell death, reduction in algal biomass, and loss in photosynthetic pigments were measured to investigate the cytotoxic effects of ZnO NPs on H. pluvialis. Extracellular and intracellular changes in algal cells resulted from the treatment of ZnO NPs were demonstrated through optical, scanning, and transmission electron microscopic studies. Results SEM-EDX spectrum evidenced the accumulation of ZnO NPs in algal biomass and ICP OES results reported a significant (p < 0.05) dose- and time-dependent accumulation of zinc in algal cells from 24 h for all the tested concentrations of ZnO NPs (10–200 μg/mL). Further, the study showed a significant (p < 0.05) dose- and time-dependent growth inhibition of H. pluvialis from 72 h at 10–200 μg/mL of ZnO NPs. The morphological examinations revealed substantial surface and intracellular damages in algal cells due to the treatment of ZnO NPs. Discussion The present study reported the significant cellular accumulation of ZnO NPs in algal cells and the corresponding cytotoxic effects of ZnO NPs on H. pluvialis through the considerable reduction in algal cell viability, biomass, and photosynthetic pigments together with surface and intracellular damages.
Keywords: Haematococcus pluvialis; Zinc oxide nanoparticles; Algal growth inhibition; Cytotoxicity